Examining the Relationship between Vaping and Smoking among Texas High School Students - Odeyemi, Joseph Olufemi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Over the last decade, e-cigarettes have grown in popularity, surpassing cigarettes as the most widely used tobacco product among adolescents. Current evidence suggests that using e-cigarettes (vaping) is less harmful than smoking cigarettes; however, vaping has been linked to severe health consequences and an increased likelihood of transitioning to cigarettes. The upward trend of vaping is infrequently studied in concert with the prevalence of cigarette smoking. The objective of this study is to explore the prevalence of e-cigarette use and to assess potential associations with cigarette smoking among Texas adolescents.Subjects and Method: This study analyzed data on the prevalence of vaping and cigarette smoking among high school students from the 2019 Texas Youth Risk Behavior Survey (YRBS), a cross-sectional survey with a sample size of 2032. Participating schools were selected using a multi-level cluster sampling technique and variables of interest were measured using a stan-dardized self-administered questionnaire. The t-test and chi-square tests were used to determine significance of associations between estimates.Results: Almost one in five respondents (18.7%) reported vaping. Non-Hispanic White students (p< 0.001), bisexual students (p < 0.001) and students in the higher grades were more likely to report e-cigarette use. Overall, cigarette smoking appeared to be on the decline in contrast to e-cigarette use and there was a positive association between cigarette smoking and vaping (p < 0.001).Conclusion: The high prevalence of vaping among Texas high school students is a call to action. Halting the upward trend of e-cigarette use is a priority as these products predispose adolescents to significant morbidity.